Love those trains - Whitmore, James; Lipscomb, James (WQED/Pittsburg : National Geographic Society, 1984)
Presents a nostalgic jouney into the world of trains. Travels aboard the Orient Express as it wines and dines the elite, the Guayaquil'Quito Train which transports rooftop passangers through the Andes, and the Salad Bowl Express which ships fresh produce from California to New York. Also shows the 150th anniversary celebration of the John Bull, the world's oldest operable steam engine.
Keywords: Railroads